Entrepreneurs and the State in the Italian Film Industry, 1919–1935 - Nicoli, Marina (Business History Review, 2011)
During its early years, entrepreneurs in the Italian film industry maintained a complicated relation with the state. The arrangements between the joint-stock company Società Anonima Stefano Pittaluga and the Italian government in the interwar period were typical. Initially, Italian banks financed productions, despite the difficulties entailed in assessing a film's potential profitability. Following the rise of Benito Mussolini, the state invested in the industry, viewing it as a means of building nationalism and shaping the country's culture. While the deal was disastrous for the quality of the films, it nevertheless enabled filmmakers to gain technical experience and acquire production facilities that they were later able to put to better use.
Keywords: Business History and gender